Виживаність рослин та урожайність зерна гречки залежно від агротехнічних заходів вирощування - Ткаліч, Ігор Дмитрович; Tkalich, Ihor; Гирка, Анатолій Дмитрович; Hyrka, Anatolii; Ткаліч, Юрій Ігоревич; Tkalich, Yurii; Бочевар, Ольга Володимирівна; Bochevar, Olha; Сидоренко, Юрій Якович; Sydorenko, Yurii (Інститут зернових культур, 2019)
Встановлено, що боронування посівів гречки середніми боронами можна проводити після сівби, по сходах і до початку бутонізації. Шляхом правильного встановлення строків і кратності боронування посіви гречки можна очистити від бур’янів на 77–90 % і таким чином добитися підвищення врожайності зерна майже на 31 %. Вирощування гречки в посівах з міжряддями 45 см зумовлює підвищення рівня урожайності порівняно з рядковим, але вибір способу сівби необхідно робити з урахуванням можливостей господарства та економічної доцільності. Дослідження показали, що при вирощуванні гречки ефективним заходом є досходове і післясходове боронування посівів (у фазі 1–2 листків або на початку бутонізації) залежно від часу появи бур’янів. При вирощуванні гречки з міжряддями 45 см, крім боронування, у визначенні строки потрібно зробити два-три міжрядних обробітки, останній з підгортанням рослин у рядках. Після появи сходів посіви гречки можна боронувати без втрат, але при цьому норма висіву має становити 4 млн схожих насінин/га. It is established that the harrowing of buckwheat crops with medium harrows can be carried out after seeding, on germinated seedlings and before budding stage. By correctly setting the harrowing time and their multiplicity, we can clean off the buckwheat crops from weeds by 77–90 %, thereby increase the grain yield for almost 31 %. Growing buckwheat with 45 cm space between the rows leads to an increase in grain yields compared to the 15 cm space between the rows, but the choice of sowing method must be made taking into account the possibilities of farms and their economic feasibility. The experiments were carried out at «Svitanok» LLC (Novomoskovs’kyi district, Dnipropetrovs’k region) during 2010–2012. The soil of the experimental plots – ordinary, middle loamy chernozem. The humus content in the arable layer varies from 4.0 to 4.2 %. The gross content of nutrients in the arable layer of chernozem varies within the following limits: nitrogen – from 0.23 to 0.26 %, phosphorus – from 0.11 to 0.16 %, potassium – from 2.0 to 2.5 %. The results of the research show that the growth and development of buckwheat plants largely depends on the density of their planting in the crop and placement on the area. Increasing the seeding rate from 2.5 to 5.0 million of germinated seeds/ha and expanding the row spacing from 15 to 45 cm reduces the area of nutrition, increases the density and uneven placement of plants in the row. This increases competition between plants, leads to a decrease in their survival during the growing season by 5.8–19.8 and 6.1–15.7 %, respectively, and productivity. The overall survival of buckwheat depending on the timing of harrowing is: during the sprouting – 44,2–52,8 %, in the stage of 1–2 leaves – 48,6–59,6 %, budding – 51,2–63,6 %, in stage of 1–2 leaves and budding – 43.2–50.0 %. Narrowing of space between the rows within the same seeding rate increases the field germination of seeds and survival of plants by 3.4–4.5 and 2.4–2.9 %, respectively, due to a more even distribution of them over the feeding area. Harrowing on germinated seedlings leads to a significant liquefaction of crops due to the uprooting, damaging and covering the plants with soil by the harrow teeth. The greatest loss of plants (27.4–35.6 %) is observed during harrowing of BZSS-1 harrows on germinated seedlings, smaller (18.7–26.7 %) – in phase of 1–2 leaves and the smallest (18.0–22, 4 %) – at the beginning of budding stage. In the case of double harrowing of buckwheat in the phase of 1–2 leaves and at the beginning of budding, 32.7–45.3 % of plants perished, which should be taken into account when established the seeding rate, depending on the number and terms of harrowing crops. With increasing seeding rate, weediness of buckwheat crops in both sowing methods is reduced by 1.5–3.4 times. Moreover, if such crops are harrowed before the emergence of seedlings, the number of weeds decreases by 1.5–1.9 times, if after – by 2.6–3.6 times. The positive effect of harrowing on the buckwheat yield depends on the seeding rate. Both sowing methods (seeding rate of 2.5–3.0 million germinated seeds/ha) yielded high grain yield (1.53–1.83 t/ha) during harrowing after sowing and in the phase of 1–2 leaves or budding, which depended on the time of the emergence of the weeds. Harrowing in these variants on germinated seedlings and in three terms caused considerable damage to the buckwheat plants, which is two years out of three, as a result – a decrease in grain yield by almost 26–31 %. Three-time harrowing of sowing at 15 cm space between the rows before germination, in the phase of 1–2 leaves and budding, based on the sowing rate of 4 million germinated seeds/ha, provided a grain yield of 1.74 t/ha, almost the same as in the best variants in 45 cm space between the rows with a sowing rate of 2.5–3.0 million germinated seeds/ha (1.81–1.83 t/ha). Wide-row buckwheat crops produced the higher grain yields than crops with 15 cm space between rows, only in the case of inter-row cultivation. On average, during the years of research, the exclusion of inter-row cultivations from growing system of wide-row crops has led to a decrease in grain yields compared to the narrow-row crop (seeding rate of 2.5–3.0 million germinated seeds/ha) by 0.20–0.21 t/ha.
Survival rate of plants and grain productivity of buckwheat depending on agrotechnical measures of cultivation
Keywords: гречка; buckwheat; боронування; harrowing; способи сівби; sowing methods; норми висіву насіння; seeding rates; урожайність зерна; grain yield